GAMBARAN PELAYANAN PRIMA RADIOLOGI DI INSTALASI RADIOLOGI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - Asih Puji Utami; Kesawa Sudarsih; Maulina Cahya Rochimayati (JRI (Jurnal Radiografer Indonesia), 2018)
Service in the field of radiology is one aspect that must be considered by the Yogyakarta Panti Rapih Hospital to improve service quality. Based on a preliminary study of the results of the questionnaire with a sample of 20 respondents who have done 2 of them, namely as many as three respondents disagree about the waiting time for all types of checks to get very fast results, a respondent does not agree on speed in providing services, this study aims to find out Overview of Prima Radiology Services at the Radiology Installation of Panti Rapih Hospital in Yogyakarta. This type of research is quantitative descriptive with a cross sectional study approach. The study was conducted by taking a sample of 97 respondents by distributing questionnaires to some patients. After the data collected will then be analyzed using the SPSS program (Statistical Product and Service Solution) version 22. Results: The results of the study based on the ability variable were 67% agreed. Based on attitude variables, as many as 82.5% agreed. Based on appearance variables, 57.7% agreed. Based on the attention variable as much as 84.5% stated strongly agree. Based on the action variable as much as 80.4% said they agreed, based on the variable responsibility, 83.5% agreed. Based on the 6 aspects of excellent service, it can be concluded based on good categories if the total score is baik 90 and not good if the total score is ≤ 90, so that the score is 81.4% good, and 18.6% is not good. Radiology Installation of Panti Rapih Hospital in Yogyakarta should provide information on taking X-rays readings before and after the examination, it is necessary to increase patience with patients, be able to control emotions while providing services, have a sense of empathy for patients, provide fast service